Literature Review: Kombinasi Strategi Pemasaran Konvensional dan Digital Dengan Teknologi Qr Code - Supandi, Dedi; Gaffur, Bardatul; Nurhaliza; Fiarani, Mesil (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This research is a literature review aimed at analyzing the effectiveness of combining conventional marketing strategies, digital marketing, and the use of QR Code technology in enhancing the marketing performance of business actors, particularly MSMEs. The study was conducted using a descriptive method with secondary data sources from previous research over the last ten years. The analysis results show a shift in marketing patterns from conventional to digital, but conventional methods remain relevant for certain segments. The integration of both is proven to be more effective compared to using either strategy separately. Additionally, QR Code technology serves as a digital enabler that bridges offline promotional materials with digital access, makes it easier for consumers to obtain product information, increases transaction efficiency, and expands marketing reach. Overall, the combination of conventional marketing strategies, digital marketing, and QR Code technology becomes an ideal approach for business actors to increase competitiveness and expand the market in the digital business era.